2022
DOI: 10.3390/land11020290
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Contamination Management Caused by Copper and Zinc Cations Leaching and Their Impact on the Hydraulic Properties of a Sandy and a Loamy Clay Soil

Abstract: Soil hydraulic properties are crucial to agriculture and water management and depend on soil structure. The impact of Cu and Zn cations on the hydraulic properties of sandy and loamy clay soil samples of Central Greece, was investigated in the present study. Metal solutions with increased concentrations were used to contaminate the soil samples and the effect on hydraulic properties was evaluated, demonstrating the innovation of the current study. The soil samples were packed separately into transparent column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 56 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…In general, copper is the most crucial plant growth and development micronutrient. In addition, it helps to increase plants' photosynthesis process and respiration (Angelaki et al 2022;Scott-Fordsmand et al 2022). In this study, copper concentration varies from 8.65 to 18.9 mg/kg with a mean of 13.30 mg/kg.…”
Section: Coppermentioning
confidence: 89%
“…In general, copper is the most crucial plant growth and development micronutrient. In addition, it helps to increase plants' photosynthesis process and respiration (Angelaki et al 2022;Scott-Fordsmand et al 2022). In this study, copper concentration varies from 8.65 to 18.9 mg/kg with a mean of 13.30 mg/kg.…”
Section: Coppermentioning
confidence: 89%
“…The soil characteristics of the study area coincide with those reported in previous works in the area [ 94 , 95 , 96 ]. Hydraulic conductivity (k) coupled with the low CEC (12.7 Cmol/kg), together with the characteristics of the sludge and soils, indicate a higher concentration of metal(loid)s in the leachates generated in the sludge; however that high concentration of metal(loid)s in the leachates would not modify particle aggregation or soil structure [ 97 ]. The low CEC may be due both to the low colloid content of the soil and to the nature of the clay minerals present (chlorite and illite).…”
Section: Discussionmentioning
confidence: 99%
“…The weakly acidic character and low carbonates, CEC, and colloid content of the soils favor the mobility of contaminant elements [ 97 ]. It has been shown [ 98 , 99 ] that the accumulation of metal(loid)s in a soil is controlled by processes such as adsorption, sorption, and/or complexation in colloids (clay minerals, iron, and/or manganese oxides, and organic matter) as well as by co-precipitation with other elements.…”
Section: Discussionmentioning
confidence: 99%
“…Having a high content of organic matter and nutrients important for plants, such as nitrogen, ammonium, potassium and zinc, improving soil fertility, urban sewage sludge contributed to improving some physical, chemical and biological properties of the soil, including soil fertility, and is able to be used to condition agricultural soils. Over time, researchers have studied the effects of soil pollution with heavy metals [23][24][25][26][27][28][29][30][31][32]. In the case of the accidental pollution of agricultural land with heavy metals, the most convenient and effective cleaning method is phytoremediation.…”
Section: Introductionmentioning
confidence: 99%